Machine learning and deep learning approaches for detecting DDoS attacks in cloud environments - Khan, Muhammad Asif; Mohd Faizal, Ab Razak; Zafril Rizal, M. Azmi; Ahmad Firdaus, Zainal Abidin; Nuhu, Abdul Hafeez; Hussain, Syed Shuja (American Scientific Publishing Group (ASPG), 2025)
Distributed Denial of Service (DDoS) attacks pose a significant threat to cloud computing environments, necessitating advanced detection methods. This review examines the application of Machine Learning (ML) and Deep Learning (DL) techniques for DDoS detection in cloud settings, focusing on research from 2019 to 2024. It evaluates the effectiveness of various ML and DL approaches, including traditional algorithms, ensemble methods, and advanced neural network architectures, while critically analyzing commonly used datasets for their relevance and limitations in cloud-specific scenarios. Despite improvements in detection accuracy and efficiency, challenges such as outdated datasets, scalability issues, and the need for real-time adaptive learning persist. Future research should focus on developing cloud-specific datasets, advanced feature engineering, explainable AI, and cross-layer detection approaches, with potential exploration of emerging technologies like quantum machine learning.